Dampak Pandemi Covid - 19 Terhadap Harga Saham Pada Sub Sektor Telekomunikasi Yang Terdaftar Di BEI - Dyah Atika Mahanani; Ida Aryati D P W; Ratna Damayanti (FEB Universitas Sultan Ageng Tirtayasa, 2021)
ABSTRACTPurpose of this research is to find out how big the difference stock prices in Telecommunications Sub-Sector before and after statement of Covid-19 Pandemic in Indonesia. Population in this study was taken from 6 companies in Telecommunications Sub-Sector listed on Indonesia Stock Exchange. Sampling technique in this study using purposive sampling technique, resulting in number of samples that meet criteria of this study in form of 4 telecommunications companies including PT. Telkom Indonesia (Persero), Tbk, PT. XL Axiata, Tbk, PT. Smartfren Telecom, Tbk, and PT. Indosat, Tbk. Secondary data source of share prices from companies in Telecommunication Sub-Sector obtained through official website of Indonesia Stock Exchange (IDX) (www.idx.co.id) in form of closing price data from before and after Covid-19 pandemic in Indonesia. Results show that there is a significant difference between stock prices before and after Covid-19 pandemic in Indonesia.